Analisis Pengaruh Kinerja Keuangan Perbankan Terhadap Harga Saham PT. Bank Rakyat Indonesia, TBK - Ovi Amala; Ladi Wajuba Perdini Fisabilillah (Universitas Negeri Surabaya, 2021)
The purpose of this study is to find out partially and simultaneously whether the financial performance of banks with variables CAR, NPL, ROA, LDR affect the development of stock prices at PT. Bank Rakyat Indonesia, Tbk in 2008-2020. The data used is secondary data in the form of annual financial reports at PT. Bank Rakyat Indonesia, Tbk for 13 years, with a quarterly period starting from 2008-2020. The sample used is state-owned banking with high liquidity, namely PT. Bank Rakyat Indonesia, Tbk. The data analysis test used is Regression Analysis in the form of time series data with Eviews 10. The tests include the Classical Assumption Test in the form of Normality Test, Autocorrelation Test, Multicollinearity Test, Heteroscedasticity Test and Multiple Linear Regression Test in the form of simultaneous F-test and partial T-test. The results showed that the CAR, NPL, ROA and LDR variables together had an effect on stock prices of 87.47%. Partially, the CAR and ROA variables have a significant positive effect, while the LDR variable has a positive and insignificant effect, for the NPL variable it has a negative and significant effect on stock prices.